TRACER STUDY LULUSAN JURUSAN ANGKUTAN LAUT DAN KEPELABUHANAN POLITEKNIK ILMU PELAYARAN MAKASSAR - Ahmad Fauzi; Agus Sulistiono; Jumriani Jumriani; Yeti Komalasari (JURNAL VENUS, 2015)
The objectives of this study was to determine how the characteristics of alumni of Port and Shipping Management and The relevance of the curriculum according to the needs of the workforce which incluoes waiting time to get a job, employment status, occupations, income, how to get a job, educational background relevance to the work, and the relevance of the curriculum to the world the work. The location of this research was Makassar Merchant Marine Polytechnic, Shipping Lines and the Port Authority. There were 60 questionnaires returned by the alumni of the 162 alumni who have been sent. The collected data were analyzed using SPSS 13. In analyzing the data, the he used the technique of triangulation. The results of this study are (1) the characteristics of alumni KALK have a job in the shipping company, PT. Pelindo, Lecturer, Department of Transportation , Port Authority , Airport , Freight Forwarding , Syahbandar . (2) Have a GPA between 3:00 - 3.90 (3) the relevance of educational background is very relevant to the type of work (4) the relevance of the curriculum to the world of work needs to be evaluated.